PENGARUH DIETARY APPROACHES TO STOP HYPERTENSION TERHADAP METABOLIC SYNDROME - Sarbini, Dwi; Septiyana, Nur Azizah Dewi; Pratiwi, Winda Wahyu (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Metabolic Syndrome (MetS) is a batch of cardiovascular disease and type 2 diabetes mellitus risk factors. The incidence of MetS in Indonesia for 5 years (2013-2018) has increased in patients with central obesity (4,4%), hypertension (8,31%), hyperglycemia (0,5%), hypertriglyceridemia (3%), and decreased HDL cholesterol (1,4%). One of the causes of the increased risk of MetS is the bad diet.Objectives: The aim of the literature review is to examine the effect of dietary approaches to stop hypertension (DASH) on MetS.Methods: Searched the keyword by PICO method (adults, elderly, DASH, hypertension, diabetes mellitus and MetS). The sourced for literature review was Pubmed database (https://pubmed.ncbi.nlm.nih.gov/). Articles were written in English that free full text, published in 2012–2022, the type of research was randomized controlled trial, the subjects ware sufferers of MetS, hypertension, diabetes mellitus, adults, and elderly, as well as reputed Scopus Q1-Q4 had reviewed. Six articles has been chosed from 632 articles that were found based on the criteriaResults . The results of the review article showed that DASH can reduce waist circumference (WC) at 67%, blood pressure (BP) at 67%, triglycerides at 67%, fasting blood glucose (GDP) at 67% and increase HDL-cholesterol at 33%. The results of statistical analysis showed a significant decrease in WC (67%), BP (33%), triglycerides (17%), and GDP (33%).Conclusion: Based on this literature review, it was concluded that DASH can reduce MetS risk factors.Keywords : Adult; Diet DASH; MetS. ABSTRAKLatar belakang: Metabolic Syndrome (MetS) merupakan kumpulan faktor risiko cardiovascular disease dan diabetes melitus tipe 2. Kejadian MetS di Indonesia selama 5 tahun (2013-2018) mengalami peningkatan pada penderita obesitas sentral (4,4%), hipertensi (8,31%), hiperglikemia (0,5%), hipertrigliseridemia (3%), dan penurunan kolesterol high density lipoprotein (HDL) (1,4%). Salah satu penyebab peningkatan risiko MetS adalah pola makan yang salah.Tujuan: mengkaji pengaruh dietary approaches to stop hypertension (DASH) terhadap MetS.Metode: Pencarian kata kunci menggunakan metode PICO (dewasa, lansia, DASH, hypertension, diabetes mellitus dan MetS). Literature review ini menggunakan sumber database Pubmed (https://pubmed.ncbi.nlm.nih.gov/). Artikel yang termasuk dalam kriteria inklusi dan eksklusi adalah artikel free full text menggunakan Bahasa Inggris, terbit tahun 2012–2022, jenis penelitian randomized controlled trial, subjek merupakan penderita MetS, hipertensi, diabetes melitus, orang dewasa dan lansia, serta bereputasi Scopus Q1-Q4.Hasil: Diet DASH dapat menurunkan waist circumference (WC) sebesar 67%, tekanan darah (TD) sebesar 67%, trigliserida sebesar 67%, glukosa darah puasa (GDP) sebesar 67% dan meningkatkan HDL-kolesterol sebesar 33%. Hasil analisis statistik menunjukkan penurunan secara signifikan terjadi pada WC (67%), TD (33%), trigliserida (17%), dan GDP (33%). Simpulan: Diet DASH dapat menurunkan faktor risiko MetS.Kata Kunci : Dewasa; Diet DASH; Sindrom Metabolik